A Study of Corporate Cash Holding Behaviors during Economic Transition in China: 1999-2007 - Yuwei Fang; Qingjie XIa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
Based on a panel data of all manufacturers for the period from 1999 to 2007 in China, this paper examines the relationship between liquidity preferences of firm and external financing environment. By applying the model of cash flow sensitivity of cash, this paper reveals that (i) although all firms encounter more or less financial constraints, state-owned enterprises (SOEs) get greater access to capital market and hence display positive cash flow sensitivity of cash; (ii) the fast growth of non-SOEs intensified financial constraints (but provide large amount of cash flow which is particularly true for the firms at their initial development stage and become the major financial resource for their further development), exhibits as the substitution of saving with investment; and (iii) the impact of financial constraints on the growth of non-SOEs increases with the size of the firms, which shows higher cash flow sensitivity of cash.